2014
DOI: 10.1016/j.ultsonch.2013.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of reactive orange 4 dye using hydrodynamic cavitation based hybrid techniques

Abstract: In the present work, degradation of reactive orange 4 dye (RO4) has been investigated using hydrodynamic cavitation (HC) and in combination with other AOP's. In the hybrid techniques, combination of hydrodynamic cavitation and other oxidizing agents such as H2O2 and ozone have been used to get the enhanced degradation efficiency through HC device. The hydrodynamic cavitation was first optimized in terms of different operating parameters such as operating inlet pressure, cavitation number and pH of the operatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(72 citation statements)
references
References 36 publications
7
60
0
1
Order By: Relevance
“…However, the efficiency of H 2 O 2 in degrading pollutants can be enhanced significantly if it is used in combination with an HC system. This is because the energy imparted by the collapsing cavities drives the dissociation of H 2 O 2 into Å OH radicals, and supports their subsequent microdiffusion [1,7,34]. Furthermore, the overall performance results showed that a technique combining electric field and HC system had a significant positive effect on the decolorization of AO-7, and reduced reaction time, as shown in Fig.…”
Section: Feasibility Test Of Various Electric Field-assisted Hydrodynmentioning
confidence: 77%
See 2 more Smart Citations
“…However, the efficiency of H 2 O 2 in degrading pollutants can be enhanced significantly if it is used in combination with an HC system. This is because the energy imparted by the collapsing cavities drives the dissociation of H 2 O 2 into Å OH radicals, and supports their subsequent microdiffusion [1,7,34]. Furthermore, the overall performance results showed that a technique combining electric field and HC system had a significant positive effect on the decolorization of AO-7, and reduced reaction time, as shown in Fig.…”
Section: Feasibility Test Of Various Electric Field-assisted Hydrodynmentioning
confidence: 77%
“…In order to highlight the interactive effect of the key parameters (inlet pressure, initial pH, applied voltage, and reaction time) in the EFM-HC, three-dimensional response surfaces derived from Eq. (7) are presented in Fig. 6(A)-(F) with the independent variables being kept constant at the statistically optimized.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Solvent degradation is rarely reported so far; however, abundant studies are available in the literature for degradation of dyes in wastewaters. Li et al [24] [11]. Thus, although solvent degradation data is not available, it appears that the rate of degradation increases with increasing molar mass with respect to particular class or nature of compounds.…”
Section: Effect Of Nature Of Solventmentioning
confidence: 99%
“…In recent decades, increasing attention has been devoted to investigating this phenomenon as a tool of disinfection [24,25,26,27,28], cell disruption [29,30] and degradation of various organic compounds, e.g., pharmaceutical residues [31,32], phenols [33], pesticides [34], insecticides [35] and textile dyes [36,37]. However, most studies mainly addressed the process with regard to the synthetic wastewater containing only specific pollutants.…”
Section: Introductionmentioning
confidence: 99%